SCAR Air Operations Planning Maps series, sheet 08, Aboa to Novolazarevskaya - Skoglund, Anders (Norwegian Polar Institute, 2016)
Edition 2 of the SCAR Air Operations Planning Maps series (AOPM) sheet 08, Aboa to Novolazarevskaya. The map covers the western part of Dronning Maud Land, at scale 1:1 000 000.